Optimizing Discovery Learning to Enhance HOTS: Why Use Argumentative Worksheets? - Neni Hasnunidah; Sherly Fadhila; Berti Yolida; Meriza Nadya; Dina Maulina (Jurnal Penelitian Pendidikan IPA, 2024)
Higher Order Thinking Skills (HOTS) is very important for learners to master because they can develop the critical, analytical, and creative thinking skills needed to face complex challenges in daily life This study aims to examine the HOTS of students on the use of the Argumentative LiveWorksheet of Plant Tissue Structure through the Discovery Learning model. This type of research is a quasi-experiment using a pretest-posttest non-equivalent control group design. The subject of this study is 60 students of grade VIII of junior high school in Metro City which are divided into experimental classes and control classes. The research instrument is in the form of a HOTS essay test that measures the ability to analyze (C4), evaluate (C5), and create (C6) according to Bloom's taxonomy. In addition, questionnaire instruments are also used to find out students' responses to the learning carried out. The results showed that the experimental group that used the LiveWorksheet argumentative with the Discovery Learning model had a significantly higher HOTS score when compared to the control group. The argumentative LiveWorksheets with Discovery Learning creates a more dynamic learning environment by encouraging active student involvement in discussions, arguments, discovery, and reflective practices.